Emotional intelligence and its associated factors among case team leaders in health centers of East Gojam Zone, Northwest Ethiopia: an institutional based cross-sectional study - Endalew Minwuye Andargie; Seblewongel Gebretsadik Sertsewold; Tamiru Minwuye Andargie; Haimanot Wubale Tewabe; Asrat Kassaw; Yonas Fissha Adem; Wubshet D. Negash (BMC Health Services Research)
Abstract Introduction Poor emotional intelligence (EI) among healthcare leaders resulted in ineffective communication and collaboration, misunderstandings and conflicts with team members, poor decision-making process, increased stress and burnout, reduced patient satisfaction and, decreased team performance. Thus, this study is aimed to assess EI and associated factors among case team leaders in the public health centers of East Gojam Zone, Northwest Ethiopia. Method An institution-based cross-sectional study was performed in the East Gojam Zone among 395 case team leaders selected by a simple random sampling method. EI was measured with 40 five-point Likert items. A structured self-administered questionnaire was used to collect the data. Data was entered into Epi-Data version 4.6 and exported further into STATA version 14.0 for analysis. Multi-variable binary logistic regression model was employed to determine factors associated with EI, and statistical significance was detected with P-value < 0.05 and 95% CI. Result EI among case team leaders was low among 180 (45.6%), and high 215 (54.4%). Factors associated with EI were age with 35–39 years old [AOR = 1.21; 95% CI: (1.03–1.65)], training on EI [AOR = 1.50; 95% CI: (1.35–1.69)], 4–6 years of working experience [AOR = 1.19; 95% CI: (1.15–1.54)] & greater or equal to six years [AOR = 1.48; 95% CI: (1.36–1.59)], those who have Master and above educational status [AOR = 1.32; 95% CI: (1.18–1.75)], having stressor in the last six months [AOR = 0.75; 95% CI: (0.32–0.98)]. Conclusion and recommendation This study evidenced that larger proportion of case team leaders in the health centers of East Gojam Zone had high EI. Those case team leaders with the age of 35–39 years old, Master degree holders, trained on EI, hadn’t history of stressor in the last six months, and those who had working experience of above four years were identified as having high EI in the study area. Training on EI and stress management in the clinical setting should also be deliberated in the prospect policies.